American immunity : war crimes and the limits of international law - Hagopian, Patrick (Culture, politics, and the Cold War., 2013)
"In 2000 Congress attempted to close the jurisdictional gap with passage of the Military Extraterritorial Jurisdiction Act. The effectiveness of that legislation is still in question, however, since it remains unclear how willing civilian American juries will be to convict veterans for conduct in foreign war zones."--Publisher description.